2000
DOI: 10.1034/j.1399-3054.2000.110117.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen expression in maize seed development and germination: Regulation by phytohormones and its association with putative cell cycle proteins

Abstract: The proliferating cell nuclear antigen (PCNA) plays a fundamental role in DNA replication and repair and recently, it has been found associated to proteins that control the G1 phase of the cell cycle, such as cyclin D. Maize PCNA cDNA has been cloned and overexpressed in order to raise antibodies. The expression of PCNA has been followed during seed development and seed germination using the homologous antibodies. The protein was found at a constant level during seed development up to 48 days after pollination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Previous studies showed that PCNA expression was up-regulated in buds of pea within 4 h following a decapitation treatment that promoted bud outgrowth (Shimizu and Mori, 1998) and was downregulated in sorghum (Sorghum bicolor) axillary buds suppressed by low R:FR or defoliation . ABA had little effect on PCNA protein accumulation in maize seeds (Herrera et al, 2000), suggesting that its effects on expression may depend on the type or developmental stage of the tissue. PCNA1 is a multifunctional protein that is involved in DNA repair and also acts as a processivity factor during DNA replication (Strzalka and Ziemienowicz, 2011).…”
Section: Aba Was Not Found To Strongly Influence Sugar or Cytokinin Pmentioning
confidence: 99%
“…Previous studies showed that PCNA expression was up-regulated in buds of pea within 4 h following a decapitation treatment that promoted bud outgrowth (Shimizu and Mori, 1998) and was downregulated in sorghum (Sorghum bicolor) axillary buds suppressed by low R:FR or defoliation . ABA had little effect on PCNA protein accumulation in maize seeds (Herrera et al, 2000), suggesting that its effects on expression may depend on the type or developmental stage of the tissue. PCNA1 is a multifunctional protein that is involved in DNA repair and also acts as a processivity factor during DNA replication (Strzalka and Ziemienowicz, 2011).…”
Section: Aba Was Not Found To Strongly Influence Sugar or Cytokinin Pmentioning
confidence: 99%
“…Towards this end, we isolated two avocado cDNAs encoding mitotic A-and B-type cyclins, together with a third cDNA encoding a putative proliferating cell nuclear antigen (PCNA), serving as a G1-S transition state marker (Citterio et al 1992;Herrera et al 2000) and monitored their developmental expression proWles in NF and SF tissues. Secondly, we performed parallel developmental studies of cell division (cell number) and cell expansion (cell area).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequent that plant genomes contain two PCNA genes, in contrast to PCNA pseudogenes normally found in mammalian cells. Plant PCNA forms a homotrimeric complex (Sanchez et al 2002;Strzalka et al 2009) that binds to various cyclin-CDK complexes (Herrera et al 2000;Sanchez et al 2005). In agreement with the hypothesis of serving as a sliding platform to other proteins, in vitro assays showed that PCNA-associated cyclin/CDK activity phosphorylates DNA polymerase a.…”
Section: Pcnamentioning
confidence: 80%